The Effect of Company Size, Leverage, Profitability, and Company Growth on Company Value - Muhamad Taufiq; Sumiyarti; Pardomuan Sihombing (International Journal of Economics Accounting and Management, 2025)
The purpose of this study is to examine the effect of Size, leverage, profitability, and company growth on company value, with interest rates as a moderating variable. The population in this study consists of companies in the coal sub-sector listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The sampling technique used is purposive sampling, resulting in a total of 14 research samples being used in this study. The data analysis technique used in this study is panel data regression. The analysis results show that Size has a negative and significant effect on Firm Value; Leverage has a positive but insignificant effect on Firm Value; Profitability has a negative and significant effect on Firm Value; Firm Growth has a positive but insignificant effect on Firm Value; Interest Rate has a negative but insignificant effect on Firm Value; Interest Rate cannot moderate Size on Firm Value; Interest Rate cannot moderate Leverage on Firm Value; Interest Rate can moderate Profitability on Firm Value; Interest Rate can moderate Firm Growth on Firm Value.